High-Resolution and High-Precision Weighted Essentially Non-Oscillatory Scheme for Compressible Flow Simulations (Advances in Applied Mathematics and Mechanics, 2024)
In this paper, a new high-resolution WENO-MIM scheme that can achieveoptimal accuracy at high-order critical points is developed. The nonlinear weight function of the new scheme can be obtained by adding a freely adjustable term with a parameter $λ$ to the mapping function of the WENO-IM scheme. A sufficient conditionshows the shock-capturing ability of WENO-MIM will be enhanced with the increaseof $λ.$ The parameter $λ=467$ obtained from experience can guarantee the new schemeachieves high resolution. Numerical example results show that the present scheme canachieve optimal accuracy at high-order critical points and perform significantly betterthan other WENO schemes in highly efficient computing of various compressible fluidproblems.